REMOVAL OF HYDROGEN SULPHIDE CONTENT FROM BIOGAS BY ATOMIZING OF ALKALI SOLUTION - MOLNÁR, Éva; RIPPEL-PETHŐ, Dóra; HORVÁTH, Géza; BOBEK-NAGY, Janka; BOCSI, Róbert; HODAI, Zoltán (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Our energy requirements increased significant in the last decades. For this reason the potential utilization of renewable energy sources come into view. Biogas is a kind of renewable energy sources. Purification of raw biogas is essential prior to use. Mainly the hydrogen sulfide content of gas is very harmful. It can cause corrosion in compressors and engines. Furthermore, sulfur dioxide and sulfur trioxide are formed from hydrogen sulfide due to combustion, which similarly corrosive present of water and toxic like hydrogen sulfide. We examined the hydrogen sulfide absorption from biogas model gas mixtures (CO2, H2S, N2) based on alkali competitive chemisorption technology.